KEDUDUKAN HADIS MURSAL DALAM KAJIAN HADIS - Muizah Hasanah; Husnul Maab (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2021)
This paper talks about the position of mursal hadith in the study of hadith science. The discussion is focused on the definition, causes, levels and the law of proving using the Mursal hadith. Mursal hadith is a category of hadith that is included in the position of hadith dho’if. Mursal hadith is a hadith that reaps differences of opinion among hadith scholars. It is hoped that knowing the position of the mursal hadith can help in selecting the hadith to be used as evidence. The method used in this research is descriptive method. The analysis will be carried out using the type of data in the form of qualitative with library research (library research). The sources used in this study are hadith books, books, journals or articles related to the title of the discussion.